2013
DOI: 10.1039/c3tc00005b
|View full text |Cite
|
Sign up to set email alerts
|

Sub-picosecond delocalization in the excited state of conjugated homopolymers and donor–acceptor copolymers

Abstract: In this feature article, we review and examine evidence that the primary photoexcited species in conjugated polymers is considerably delocalized. Localization occurs via a series of complex relaxation mechanisms on the <200 femtosecond time scale. We show that short-lived delocalization in the neutral excited state and charge separated state of bulk heterojunction blends might play an essential role in ensuring efficient formation of free charge carriers for photovoltaic applications. Finally, the additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
143
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(150 citation statements)
references
References 160 publications
(270 reference statements)
7
143
0
Order By: Relevance
“…Transport in such devices is usually attributed to incoherent hopping 1 , although there is increasing evidence of a subpicosecond coherent contribution. [2][3][4][5] The mobility of singlet excitons is derived mainly from the Coulombic coupling between chromophores, consistent with the fundamental excitations being Frenkel-type excitons where the electron and hole remain bound to the parent molecule. However, in tightlypacked π-stacked organic crystals, such as those corresponding to a multitude of perylene-based dyes [6][7][8] , the close proximity of neighboring molecules leads to significant charge transfer (CT) between chromophores through the spatial overlap of their frontier molecular orbitals.…”
Section: Introductionmentioning
confidence: 62%
“…Transport in such devices is usually attributed to incoherent hopping 1 , although there is increasing evidence of a subpicosecond coherent contribution. [2][3][4][5] The mobility of singlet excitons is derived mainly from the Coulombic coupling between chromophores, consistent with the fundamental excitations being Frenkel-type excitons where the electron and hole remain bound to the parent molecule. However, in tightlypacked π-stacked organic crystals, such as those corresponding to a multitude of perylene-based dyes [6][7][8] , the close proximity of neighboring molecules leads to significant charge transfer (CT) between chromophores through the spatial overlap of their frontier molecular orbitals.…”
Section: Introductionmentioning
confidence: 62%
“…A quantitative understanding of exciton migration in conjugated polymers is important for applications in organic photovoltaics, lightemitting diodes and lasers [1][2][3][4][5] . In polymer films excitons migrate along conjugated chains as well as between chains [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…A detailed mechanistic understanding of primary charge generation dynamics is of key fundamental importance in the development of organic solar cells, and we propose it to be generally important in photoinduced charge-transfer processes in condensed matter. Recent spectroscopic measurements on organic photovoltaic systems have reported that charged photo excitations can be generated on r100-fs time scales [2][3][4][5][6][7][8][9][10] ; however, full charge separation to produce photocarriers is expected to be energetically expensive given strong Coulombic barriers due to the low dielectric constant in molecular semiconductors. Nonetheless, experiments by Gélinas et al 11 in which Starkeffect signatures in transient absorption spectra were analysed to probe the local electric field as charge separation proceeds, indicate that electrons and holes separate by B40 Å over the first 100 fs and evolve further on picosecond time scales to produce unbound charge pairs.…”
mentioning
confidence: 99%